Changes in rainfall patterns in the eastern area of La Pampa province, Argentina - Eduardo Mario Sierra (Revista Ambiente & Água, 2012)
The eastern area of the Province of La Pampa, Argentina lies in a transition zone between the humid temperate climate stretching east and the steppe climate stretching west. The area is very sensitive to changes in precipitation patterns, especially when changes are sudden and there is no time to take adaptive measures to cope with the impacts of climate change. In such cases, agricultural production and the balance of the environment are threatened by potential disaster. In order to determine the long-term occurrence of such phenomena, long-term annual precipitation series (1921–2009) from 14 stations in the study area were analyzed using the procedure of hydrometeorological series segmentation. The results for the study period show a succession of abrupt increases, with annual precipitation increasing by about 30%. Each increase in rainfall can be seen as a fostering factor for the expansion of crop planted area in the following years. However, in recent years, there has been an abrupt and significant decrease in precipitation with a marked return to the conditions that prevailed at the beginning of the period. Because agriculture intensified during the period of increased rainfall, the carrying capacity of the environment could be exceeded if rainfall continues to decrease over a long period of time, causing a decline in production accompanied by environmental degradation.